Report on industrial attachment with E-Cube Pte. Ltd - Ng, Andrew Keong. (2008)
Direct-digital-control (DDC) systems are complex and extensive systems empowered to manage energy in building heating, ventilation and air-conditioning (HVAC) systems. It has resulted in a variety of applications, such as the detection and analysis of faults in HVAC systems, the monitoring of equipment, the verification of energy savings, and the documentation of indoor-air-quality conditions